KAFA'AH IN THE CONTEMPORARY RABITHAH ALAWIYAH COMMUNITY: THE PERSPECTIVE OF THE INDONESIAN ULEMA COUNCIL OF ASAHAN REGENCY - Yuliana, Fika; Irwan (al-Mawarid Jurnal Syariah dan Hukum (JSYH), 2025)
Purpose - This research aims to analyze the concept of kafa'ah in the Rabithah Alawiyah community in Asahan and to find out the views of the Indonesian Ulema Council (MUI) of Asahan Regency on the marriage of Syarifah with non-Sayyid. In the Rabithah Alawiyah community in Asahan, which still upholds the values of the descendants of the Prophet Muhammad SAW (Ahlul Bait), the concept of kafa'ah is often associated with the prohibition of marriage outside the Sayyid or Syarifa'h community. Methods - This research uses empirical legal methods with a qualitative approach. Data were collected through observation, interviews, and documentation with MUI Asahan Regency, members of the Rabithah Alawiyah community, and individual Syarifahs and Sayyids. Analysis was conducted by exploring legal facts directly to obtain accurate data. Findings - The results showed that in the Rabithah Alawiyah community in Asahan, Syarifah's marriage with non-Sayyids is considered to damage the nasab and not maintain family honor. This is not only because of kafa'ah considerations but also as an effort to preserve the purity of the Prophet's lineage in the contemporary era until the end. Contribution/Limitation of Research - This research provides an understanding of the dynamics of kafa'ah in the Rabithah Alawiyah community and its relevance to contemporary Islamic family law. However, this research is limited to the community in Asahan, so the findings cannot be generalized to other regions. Originality/Value - This research offers a contemporary Islamic Family law perspective on kafa'ah in marriage. The findings can serve as a reference for Islamic law academics and practitioners in understanding the concept of kafa'ah in the modern social context.